Answer:
See below
Step-by-step explanation:
Let me give you an example to help;
[tex]y = 2x + 3[/tex]
This equation is in slope - intercept form, which can be demonstrated through the following notation -
[tex]y = mx + b - Where, m = slope, and, b = y - intercept[/tex]
Now to solve for the x - intercept, we will have to propose y as 0;
[tex]0 = 2x + 3,\\2x = - 3,\\x = - 3 / 2 = - 1 and 1 / 2[/tex]
Thus the x - intercept = - 1 and 1 / 2;
* Note that you can't solve a slope intercept form equation, unless it is a system of equations, and if that is the case just let me know and I can help you out with that *